Foreign Currency as a Barrier to International Trade: Evidence from Brazil - Messer, Todd (The Review of Economics and Statistics, 2026)
This paper studies the causal effect of foreign currency dependence on international trade by exploiting Brazil and Argentina's 2008 introduction of a bilateral payments system that eliminated the U.S. dollar as vehicle currency. I identify causal effects using a triple-difference design comparing exports across municipalities with varying bank access and across destinations to control for contemporaneous shocks including the financial crisis. Firm-level analysis finds that local currency adoption increased export values significantly, with effects concentrated among non-commodity exporters. These results demonstrate that foreign currency dependence constitutes a meaningful barrier to emerging market trade.